Petrophysical Analysis to Determine Reservoir and Source Rocks in Berau Basin, West Papua Waters - Popy Dwi Indriyani; Asep Harja; Tumpal Bernhard Nainggolan (BULLETIN OF THE MARINE GEOLOGY, 2020)
Berau Basin is assessed to have same potential in clastic sediments with Mesozoic and Paleozoic ages, where reservoirs and source rocks are similar to productive areas of hydrocarbons in Northwest Shield Australia. This study aims to identify the hydrocarbon prospect zones and potential rocks zones using petrophysical parameters, such as shale volume, porosity, water saturation and permeability. Petrophysical analysis of reservoir and source rock are carried out on three wells located in the Berau Basin, namely DI-1, DI-2 and DI-3 in Kembelangan and Tipuma Formation. Qualitative analysis shows that there are 4 reservoir rock zones and 4 source rock zones from thorough analysis of these three wells. Based on quantitative analysis of DI-1 well, it has an average shale volume (Vsh) 9.253%, effective porosity (PHIE) 20.68%, water saturation (Sw) 93.3% and permeability (k) 55.69 mD. DI-2 well’s average shale volume, effective porosity, water saturation and permeability values are 29.16%, 2.97%, 67.9% and 0.05 mD, respectively. In DI-3 well, average shale volume, effective porosity, water saturation and permeability values are 6.205%, 19.36%, 80.2% and 242.05 mD, respectively. From the reservoir zone of these three wells in Kembelangan Formation, there are no show any hydrocarbon prospect.Keywords: reservoir, source rock, shale volume, porosity, water saturation, permeability, Kembelangan Formation, Tipuma Formation, Berau BasinCekungan Berau diperkirakan memiliki potensi yang sama dengan sedimen klastik yang berumur Mesozoikum dan Palezoikum, di mana reservoar dan batuan induknya memiliki kesebandingan dengan daerah produktif hidrokarbon di Paparan Barat Laut Australia. Penelitian ini bertujuan untuk mengidentifikasi zona prospek hidrokarbon dan zona potensi batuan induk dengan menggunakan parameter petrofisika, yaitu volume shale, porositas, saturasi air dan permeabilitas. Analisis petrofisika batuan reservoar dan batuan induk dilakukan pada tiga sumur bor yang terletak di Cekungan Berau yaitu Sumur DI-1, DI-2 dan DI-3 pada Formasi Kembelangan dan Tipuma. Hasil analisis kualitatif menunjukan terdapat empat zona reservoar dan empat zona batuan induk dari keseluruhan tiga sumur. Berdasarkan analisis kuantitatif, sumur DI-1 memiliki nilai rata-rata volume shale (Vsh) 9,253%, porositas efektif (PHIE) 20,68%, saturasi air (Sw) 93,3% dan permeabilitas (k) 55,69 mD. Pada sumur DI-2, nilai rata-rata volume shale 29,16%, porositas efektif 2,97%, saturasi air 67,9% dan permeabilitas 0,05 mD. Serta pada sumur DI-3, nilai rata-rata volume shale 6,205%, porositas efektif 19,36%, saturasi air 80,2%, dan permeabilitas 242,05 mD. Dari zona reservoar Formasi Kembelangan untuk tiga sumur tersebut, tidak menunjukan adanya prospek hidrokarbon.Kata Kunci: reservoar, batuan induk, petrofisika, volume shale, porositas, saturasi air, permeabilitas, Formasi Kembelangan, Formasi Tipuma, Cekungan Berau